Wanprestasi Debitur dan Perlindungan Hukum terhadap Kreditur Pemegang Hipotek Kapal - Mirza Yusuf; Tiara Amalia; Kamila Raisa; Dimas Aji; Fidelis Bentar; Yudhistira Raihan (Universitas Wahid Hasyim, 2025)
The growing activity of lending and borrowing within society demands the presence of collateral instruments that provide legal certainty and protection for creditors, one of which is through the imposition of a mortgage on sea-going vessels. This study aims to examine the imposition of ship mortgages from the perspective of collateral law in Indonesia, the forms of legal protection afforded to creditors in cases of debtor default, and the challenges that arise during the execution of the collateral object. The research method employed is normative juridical, using a literature study approach that includes legislation, legal doctrines, and court decisions. The findings show that sea-going vessels with a minimum gross tonnage of 20 m³ that are officially registered can be used as mortgage objects based on the provisions of the Indonesian Civil Code, Commercial Code, and Law Number 17 of 2008 on Shipping. A mortgage grants a preferential position to creditors, including direct execution rights and in rem rights that remain attached even if the object is transferred. Legal protection for creditors is divided into preventive and repressive measures, covering registration obligations, limiting clauses, preferential rights, droit de suite, and the executorial power of the grosse mortgage deed. The implications of this study indicate that Indonesia's legal system has provided a fairly comprehensive regulatory framework for ship mortgages, although practical challenges still exist, such as the legal status of ships under construction and ownership disputes that may hinder execution. Therefore, due diligence and institutional harmonization are necessary to strengthen the effectiveness of legal protection for creditors in maritime financing transactions.